PSO based optimal reactive power dispatch (ORPD) considering multi-contingencies - Nor Rul Hasma, Abdullah; Mahfuzah, Mustafa; Rosdiyana, Samad; Pebrianti, Dwi; Lailatul Niza, Muhammad (UTeM, 2018)
A stable power system can be subjected to voltage fluctuations due to poorly regulated reactive power flow that causes system instability. Reactive power is closely related to system voltage control, therefore, it is crucial to ensure the correct amount of reactive power is supplied to the system loads to achieve smooth power system operation and avoid voltage collapse from occurring. This paper presents the implementation of Particle Swarm Optimization (PSO) technique for solving ORPD problem considering multiple contingencies (N-m). The technique was implemented with the aim to improve voltage stability and minimize total transmission losses of the system. The IEEE 30-bus system was tested with generator outage in order to simulate the impact of disturbance to the power system transmission and distribution.